Strategy to Increase Competency of Human Resources on Good Manufacturing Practice (GMP) Of The Fishery Processing Group In Makassar City - Astaman Amir; Sajriawati Sajriawati; Andi Nur Apung Masisseng; Yeni Safitri Andi Lawi (Faculty of Agriculture Musamus University, 2019)
One of the strategic issues of marine potential management is the low quality of human resources of Marine society. This issue needs to be addressed through human resources development aimed at improving knowledge, changing attitudes and improving skills. This research aims to develop a strategy to increase human resources competency Group of fishery in Makassar. The sampling method used is nonprobability. Samples were taken using the formula Slovin with a 10% accuracy so that the samples were taken as much as 87 of 654 people. The research location is the city of Makassar chosen based on the consideration that in Makassar there are groups of processing and marketers of fishery results. The Data collected includes HR competence. Data analysis uses a combination of quantitative and qualitative analyses. The coordinates of IFAS and EFAS are in Quadrant IV which demonstrates the strategy of improving HR competence on GMP in the fishery processing group in Makassar City using the strategy of WT (Weaknesses – Treaths).